Pengembangan Media Voice E-book sebagai Upaya Penguatan Profil Pelajar Pancasila - Delusi Andes; Nurdinah Hanifah; Aah Ahmad Syahid (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
This research aims to determine a the results of the feasibility validation of the IPAS learning in the Merdeka Curriculum known as Voice E-book as an effort to strengthen the profile of Pancasila students. Voice E-books can cater to the various learning styles of students. The method used in this research is the Research and Development development method of the ADDIE model proposed by Dick and Carry in 1996. This study utilizes a five-stage approach, which includes analysis, design, development, implementation, and evaluation. The participants in this study consisted of 4th grade students from SD Negeri 1 Kebarepan, Cirebon Regency. The findings of this study have been thoroughly validated, with a material validation score of 90% and a media validation score of 99% . The learning process using Voice E-book has been validated with an impressive score of 96%, indicating excellent performance. Furthermore, the findings include the results of students' questionnaires regarding the profile of Pancasila students, which achieved a score of 92% and questionnaires on voice E-book media received a score of 93%. Thus, it can be concluded that utilizing Voice E-book media to strengthen the profile of Pancasila students is highly suitable.